Initial training of literacy teachers: mapping academic production (Práxis Educativa, 2021)
This study presents a survey of the state of the art of research on the initial training of literacy teachers. This qualitative research investigated how the topic is addressed in theses, dissertations, events and scientific journals produced between 2010 and 2020. Data collection was carried out by consulting the theses and dissertations database of the Brazilian Digital Library of Theses and Dissertations (BDTD), the Sucupira Platform, the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (Capes), the Scientific Electronic Library Online (SciELO) and scientific event websites. These publications were analyzed and categorized by the themes of initial training and literacy teachers. On the one hand, the results show that the themes of teacher training, curriculum and specific knowledge about literacy (language) were more frequent in the publications. On the other hand, the results point to the need for further research to understand the initial training of literacy teachers from the hegemonically produced discourse.Keywords: Academic production. Initial Trainiing. Literacy teachers.